2005
DOI: 10.1002/macp.200500207
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Differences Between Deuterated and Protonated Polystyrenes Evaluated Using Reversed Phase Liquid Chromatography

Abstract: Summary: Deuterated compounds are generally considered to possess very similar properties to their protonated analogues. Reversed phase liquid chromatography (RPLC) was used to measure thermodynamic interactions between deuterated and protonated n‐butyl polystyrenes and a C18 stationary phase. Significant differences in enthalpies and entropies of interaction were observed for deuterated and protonated n‐butyl polystyrenes. This is very important because many techniques, such as small‐angle neutron scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The differences in thermal properties between protonated and perdeuterated PHO may have also been influenced by the substitution of hydrogens by deuterons. While it has generally been assumed that deuteration of polymer chains has no effect on their thermodynamics, recent work by Kayillo et al and others have shown that these properties are sensitive to deuteration. , The vibrational states of protonated and deuterated molecules are significantly different as they depend on the mass of their nuclei . Due to its larger mass, the vibrational amplitude for deuterium is smaller than that for its protonated analogues, resulting in lower molar volumes and bond polarizability.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in thermal properties between protonated and perdeuterated PHO may have also been influenced by the substitution of hydrogens by deuterons. While it has generally been assumed that deuteration of polymer chains has no effect on their thermodynamics, recent work by Kayillo et al and others have shown that these properties are sensitive to deuteration. , The vibrational states of protonated and deuterated molecules are significantly different as they depend on the mass of their nuclei . Due to its larger mass, the vibrational amplitude for deuterium is smaller than that for its protonated analogues, resulting in lower molar volumes and bond polarizability.…”
Section: Resultsmentioning
confidence: 99%
“…Like small molecules, deuterated polymers are retained less than their hydrogenous counterparts in RPLC separation. Kayillo et al reported on the deuterium isotope effect in the RPLC retention of polystyrene (PS) oligomer. , They found the same trend as that observed for polybutadiene: the deuterated PS was retained less. In this study, we examined the retention of deuterated PS (d-PS) relative to hydrogenous PS (h-PS) in normal phase (NP) LC as well as in RPLC.…”
mentioning
confidence: 63%
“…Perny et al reported a discernible isotope effect in the temperature gradient interaction chromatography (TGIC) retention of polybutadiene . Kayillo et al reported on the deuterium isotope effect in the reversed phase liquid chromatography (RPLC) retention of styrene oligomer and also noticed a significant deuteration effect. , Like small molecules, the retention times for deuterated polymers are shorter than their protiated counterparts under most chromatographic conditions. The retention behavior of D-PS and H-PS was later investigated in normal phase (NP) and RPLC by Kim and co-workers .…”
Section: Main Applications Of Deuterationmentioning
confidence: 99%